Emotional Dependency in Dating Relationships and Psychological Consequences of Internet and Mobile Abuse - Estevez, Ana; Urbiola, Irache; Iruarrizaga, Itziar; Onaindia, Jaione; Jauregui, Paula (Anales de Psicología / Annals of Psychology, 2017)
<span style="color: #222222; font-family: ’Garamond’,serif; font-size: 8pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ES; mso-bidi-language: AR-SA; mso-bidi-font-size: 10.0pt;" lang="EN-US">New technologies are increasingly present in our daily lives, what makes necessary the study of their possible consequences and relationship with addictive behaviors. In this sense, adolescence is an especially vulnerable age for the appearance of risk behaviors such as addictions, as there is a tendency towards dependency at this development stage. The present study was carried out with a sample of 535 young university students in order to analyze emotional dependency in dating relationships and the psychological consequences of Internet and mobile use (such as anxious and depressive symptoms and low self-esteem), considering gender differences, the role that emotional dependency plays in their use, and the predictive role of their use on the aforementioned consequences. The results showed gender differences in mobile abuse, depression, and self-esteem. Also, emotional dependency correlated with Internet and mobile abuse, and both constructs correlated with anxiety, depression, and low self-esteem. Finally, emotional dependency predicted Internet and mobile abuse, as well as anxious and depressive symptomatology and low self-esteem. These variables also predicted mobile and Internet abuse. This study provides new keys to understanding emotional dependency and Internet and mobile abuse, and their inter-relationships and relationship with other constructs.